Injection of α-syn-98 Aggregates Into the Brain Triggers α-Synuclein Pathology and an Inflammatory Response - Du, Tingfu; Wu, Zhengcun; Luo, Haiyu; Lu, Shuaiyao; Ma, Kaili (Frontiers in Molecular Neuroscience, 2019)
Pathological aggregation of α-synuclein (α-syn) is a major component of Lewy bodies (LB) which play a central role in pathogenesis of Parkinson’s disease (PD). Differential expression of α-syn isoforms has been shown in PD. Isoform α-syn98 is generated by excision of exon-3 and exon-5 of the α-syn gene. In contrast to the canonical full-length α-syn isoform (α-syn140), little is known about function of the α-syn98 isoform. In the present study, to identify the potential role of α-syn98 protein in PD, we examined effects of exogenous recombinant insoluble α-syn98 aggregates on α-syn pathology and inflammatory responses in the midbrain. After injection of α-syn98 aggregates into the substantia nigra (SN), mice exhibited motor dysfunction accompanied by nigral dopaminergic neuron loss. In addition, α-syn98 aggregates injection resulted in a significant increase in phosphorylation of endogenous α-syn. Accumulations of α-syn were co-localized with p62 and ubiquitin, which suggests α-syn98 aggregates-induced pathology exhibits properties similar to human LB. Many glial cells were activated after α-syn98 aggregates injection. In addition, expression of NF-κB, interleukin 6 (IL6), and tumor necrosis factor alpha (TNF-α) and levels of oxidative stress increased after α-syn98 aggregates injection. Our results suggest that α-syn98 may play a crucial role in pathogenesis of PD.